2011
DOI: 10.1590/s0100-40422011000700023
|View full text |Cite
|
Sign up to set email alerts
|

Biosilicato®: histórico de uma vitrocerâmica brasileira de elevada bioatividade

Abstract: Recebido em 16/10/10; aceito em 12/2/11; publicado na web em 15/4/11 BIOSILICATE ® : HISTORICAL OF A HIGHLY BIOACTIVE BRAZILIAN GLASS-CERAMIC. This paper presents a historical of the Biosilicate ® , a bioactive glass-ceramic developed at the Vitreous Materials Laboratory of the Federal University of São Carlos, Brazil. After decades of study accomplished with bioactive glasses and glass-ceramics, Biosilicate ® results from a natural evolution and has similar bioactivity index, but far superior mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
0
11
0
18
Order By: Relevance
“…This may be related to the possible higher pH of the medium in the samples containing the higher concentration of Biosilicate V R extracts. 28 Liu et al 17 observed that the pH may be a determining factor in cell proliferation. These researchers showed that the highest concentration of extracts of a bioactive borosilicate glass scaffold (100%) presented a culture medium with high pH, and this induced a greater inhibition of proliferation of goat bone marrow stroma cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the possible higher pH of the medium in the samples containing the higher concentration of Biosilicate V R extracts. 28 Liu et al 17 observed that the pH may be a determining factor in cell proliferation. These researchers showed that the highest concentration of extracts of a bioactive borosilicate glass scaffold (100%) presented a culture medium with high pH, and this induced a greater inhibition of proliferation of goat bone marrow stroma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, osteoblast and fibroblast proliferation was reduced in the cells exposed to high concentration of the biomaterial (100%). This may be related to the possible higher pH of the medium in the samples containing the higher concentration of Biosilicate® extracts 28. Liu et al17 observed that the pH may be a determining factor in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto a introdução de cristalinidade no material reduziria seu índice de bioatividade e, com isso, surgia um novo desafio para o grupo de pesquisadores brasileiros [140] . Em 2003, esse mesmo grupo conseguiu desenvolver e patentear uma vitrocerâmica particulada e altamente bioativa, denominada Biosilicato® [141] .…”
Section: Bio Vitrocerâmicasunclassified